Sosialisasi SIMDES Sarana Pelestarian, Pemberdayaan dan Pengintegrasian Lembaga Adat Desa Balongmojo - Oktaviani Permatasari; Wyda Lusiana; Mokhammad Ridha; Fajar Budiyanto; Khasbulloh Huda; Irwan Swandana; Mohamad Johan Efendi (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
The aim of IT-based village community service activities in Balongmojo Village, Puri District, Mojokerto Regency, East Java is to increase understanding and skills of village traditional institutions as a means of preserving, empowering and integrating Balongmojo village traditional institutions with the SIMDES application. The problem with the Balongmojo Village traditional institution is that the knowledge of the village traditional institution administrators regarding IT and computer-based management skills is still not advanced, so all the activities of the Balongmojo village traditional institution have not been well documented. The implementation method used is utilizing the SIMDES Balongmojo application, training and mentoring regarding understanding for village administrators regarding skills in using the IT-based SIMDES application. The results of this Community Service are the IT-based SIMDES application and increased understanding and skills of village traditional institution administrators on how to collect and document all activities of village traditional institutions in Balongmojo.